Development and application of vibrating dynamic culture system for mouse oocytes and embryos - Liu, Qinli; Zhao, Sen; Zhou, Jian; Shi, Yu; Ye, Chongyang; Huo, Bo (Frontiers in Veterinary Science, 2025)
BackgroundMammalian oocytes fertilization and early embryos development primarily take place in the fallopian tube, which not only provides nutrients but also offers a suitable mechanical environment. The current culture system for oocytes and embryos in assisted reproductive technology is static, leading to weak developmental potential and an implantation rate of only 30%-40%. It is speculated that the low developmental potential may be due to the significant difference between the static culture method and the in vivo dynamic mechanical environment of the embryos. However, the mechanisms through which mechanical stimulation affects the in vitro maturation of oocytes and early embryos development remain unclear. This study aimed to investigate how vibrational stimulation affects both nuclear maturation efficiency and the subsequent parthenogenetic developmental competence of mouse oocytes.Materials and methodsThis study designed and fabricated a vibration loading device that simulates the in vivo mechanical environment of the fallopian tube. Furthermore, a numerical simulation was performed to study the effects of different loading parameters (vibration frequency and vibration amplitude) on the fluid shear stress (FSS) in the device. Immature mouse oocytes were cultured in static or vibrating (3 Hz, 6 Hz, or 10 Hz) conditions. The maturation rate, embryos compaction rate and formation rate of parthenogenetic blastocysts were compared.ResultsThe numerical simulation results showed that the average wall fluid shear stress was 0.09-3.2 dyne/cm2 when the vibration frequency was 3–10 Hz and the vibration amplitude was 0.1–1 mm. The experiment results indicate that mechanical stimulation had no significant effect on the in vitro maturation of immature mouse oocytes compared with the static culture group. However, mechanical loading at 3 Hz, 6 Hz, and 10 Hz vibration (0.1 mm amplitude), and 3 Hz vibration (1 mm amplitude) significantly increased embryo compaction, and improved the blastocyst formation rate, thereby enhancing the developmental potential of immature mouse oocytes.ConclusionsThis study developed a vibration device to simulate the in vivo mechanical environment. The loading parameters were predicted using numerical simulations, and the experiment results showed that when the wall fluid shear stress exceeded 2.0 dyne/cm2, embryonic development potential was significantly reduced. This study provides a dynamic culture device for clinical assisted reproduction and contributes to understanding the regulatory effects and mechanisms of mechanical stimulation on the in vitro maturation of immature oocytes and embryonic development.